Implementation of Community Service Activities at the Class I Immigration Office for West Jakarta Non-TPI Specialists - Catur Susan; Khotma Rubah Khoiroh Dalimunthe (Polteknik Imigrasi, 2020)
The practice of field recognition (PPL) is one of the main educational activities at the Immigration Polytechnic. The Taruna annually will conduct this activity and can be placed anywhere throughout Indonesia. When implementing the field introduction practice Taruna is expected to apply the theory that in the learning process can be real as supporting the skills before plunging directly at the place of placement when already graduated. A taruna is not only demanded to be smart academically, the taruna formed a healthy attitude and mental to be a leader and a useful person in the future. As a community servant, the welfare and prosperity of society also became the responsibility of the cadets who would someday work with the government. One of the forms of caring for the community can be realized with the simple things like social service, Socialisai and other positive actions that can give positive influence to the community. Therefore, when implementing the field introduction practice the Taruna also conducts community devotion as a manifestation of taruna concern to the community and the environment around the area of work Unit field introduction